2017
DOI: 10.1101/162115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-method brain imaging reveals impaired representations as well as altered connectivity in adults with dyscalculia

Abstract: 2 SummaryTwo hypotheses have been proposed about the etiology of neurodevelopmental disorders: representation impairments versus disrupted access to representations. We implemented a multi-method brain imaging approach to directly compare the representation vs. access hypotheses in dyscalculia, a highly prevalent but understudied neurodevelopmental disorder in learning to calculate. We combined several magnetic resonance imaging methods and analyses, including multivariate analyses, functional and structural c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
2
3
0
Order By: Relevance
“…Out meta-analysis also characterized the distributed brain networks beyond the IPS and their directional effects observed in MLD, supporting the multifaceted cognitive impairment hypothesis (Bulthé et al, 2019;Menon, 2014;Menon et al, 2020). Besides right anterior IPS and left FG/ITG, our meta-analysis also showed consistent findings with previous meta-analyses on math processing in the right anterior insula, mPFC, left IPL/SPL, right FG, dACC, and claustrum (Arsalidou et al, 2018;Arsalidou & Taylor, 2011;Hawes et al, 2019;Kaufmann et al, 2011).…”
Section: The Differential Roles Of Right Anterior and Posterior Ips I...supporting
confidence: 87%
See 3 more Smart Citations
“…Out meta-analysis also characterized the distributed brain networks beyond the IPS and their directional effects observed in MLD, supporting the multifaceted cognitive impairment hypothesis (Bulthé et al, 2019;Menon, 2014;Menon et al, 2020). Besides right anterior IPS and left FG/ITG, our meta-analysis also showed consistent findings with previous meta-analyses on math processing in the right anterior insula, mPFC, left IPL/SPL, right FG, dACC, and claustrum (Arsalidou et al, 2018;Arsalidou & Taylor, 2011;Hawes et al, 2019;Kaufmann et al, 2011).…”
Section: The Differential Roles Of Right Anterior and Posterior Ips I...supporting
confidence: 87%
“…One leading theory about MLD is their inability to process quantity information anchored in the IPS (Bulthé et al, 2019;Dehaene & Wilson, 2007;Devlin & Price, 2007;Iuculano, 2016;Von Aster & Shalev, 2007). Consistent with this view, namely the core quantity deficit hypothesis, our analysis showed the most consistent effect in right IPS and adjacent regions including SPL and IPL in MLD compared to TD.…”
Section: The Differential Roles Of Right Anterior and Posterior Ips I...supporting
confidence: 80%
See 2 more Smart Citations
“…FMRI studies in developmental dyscalculia showed abnormal activations of, among others, the mid-posterior parietal cortex during symbolic (Mussolin et al, 2010) and nonsymbolic (Bulthe et al, 2018;Kaufmann et al, 2009a;Price et al, 2007) numerical comparisons, ordinality judgements (Kaufmann et al, 2009b), approximate calculation (Kucian et al, 2006) or simple arithmetical verification (Ashkenazi et al, 2009;Iuculano et al, 2015;Rosenberg-Lee et al, 2015) in dyscalculic children with respect to controls.…”
Section: Introductionmentioning
confidence: 99%